2021
DOI: 10.1155/2021/6687513
|View full text |Cite
|
Sign up to set email alerts
|

Gyogamdan, a Traditional Medicine Prescription, Ameliorated Dermal Inflammation and Hyperactive Behavior in an Atopic Dermatitis Mouse Model Exposed to Psychological Stress

Abstract: Psychological stress (PS) plays a significant role as an aggravating factor in atopic dermatitis (AD). The traditional medicine prescription, Gyogamdan, has been used to treat chest discomfort and mood disorders caused by PS. This study investigated the effects of an ethanolic extract of Gyogamdan (GGDE) on stress-associated AD models and the underlying mechanisms. 2,4-Dinitrochlorobenzene- (DNCB-) treated BALB/c mice were exposed to social isolation (SI) stress. The effects of orally administered GGDE (100 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…In this study, SI-AD mice exhibited increases in the total distance traveled and time spent in the center zone in the OFT, indicating hyperlocomotion behavior in this mouse model. Overall, these findings are directly in line with our previous findings that demonstrated the hyperactivity symptoms of AD mice exposed to SI stress [33]. In addition, hyperlocomotion in the SI-AD mice was also demonstrated in the social interaction test with an increase in the traveling distance, as well as a decrease in resting time.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, SI-AD mice exhibited increases in the total distance traveled and time spent in the center zone in the OFT, indicating hyperlocomotion behavior in this mouse model. Overall, these findings are directly in line with our previous findings that demonstrated the hyperactivity symptoms of AD mice exposed to SI stress [33]. In addition, hyperlocomotion in the SI-AD mice was also demonstrated in the social interaction test with an increase in the traveling distance, as well as a decrease in resting time.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have demonstrated that the SI stress model in mice is useful for the evaluation of psychological stress in AD [35]. Our previous study demonstrated that SI stress could exaggerate dermatitis and induce hyperactivity in DNCB-induced AD mice [33]. Hence, this study examined the effects of SPS in the SI-AD mouse model.…”
Section: Sps Alleviated Clinical Symptoms Of Ad In the Si-ad Micementioning
confidence: 98%
See 2 more Smart Citations